Covid and Social Distancing with a Heterogenous Population - Miltiadis Makris (University of Kent, School of Economics, 2020)
Motivated by the Covid-19 epidemic, we analyse a SIR model of an epidemic but with endogenous social distancing, and calibrate it to UK data to study various hypothetical scenarios of government intervention regarding social distancing. We explicitly take into account that (a) there is heterogeneity in the population in terms of infection-induced fatality rates and thereby private decisions on social distancing, and that (b), due to limited resources available for health services, mortality rates may depend on the stock of infected people who become seriously ill because of the infection. Simulations based on our calibrated model suggest that lockdown policies that shut down some of the essential sectors have a stronger impact on the death toll than on the evolution of infections and the level of "herd immunity" compared to policies that shut down non-essential sectors, and vice versa. Finally, there might not be an after-wave after lockdown policies that shut down some of the essential sectors are lifted.
Keywords: C61; C72; C73; H41; I12; I18; 330; COVID-19; Epidemiology; SIR model; Social Distancing; Externalities